БІОЛОГІЧНІ ТА ПСИХОЛОГІЧНІ АСПЕКТИ ВАЛЕОЛОГІЧНОЇ ПРОФІЛАКТИКИ НЕЙРОМ’ЯЗОВОЇ ДИСТРОФІЇ (Педагогіка вищої та середньої школи, 2022)
The article is about the psychological problems of the families which are bringing up an invalid child suffering from muscle dystrophy. According to the data, there are about 7500 people ill with this disease in Ukraine. It is necessary to overcome an prejudiced attitude towards invalids which had being formed by the traditions of many centuries. An invalid child should not be isolated from the community; it is also necessary to create all the conditions under which the child will be able to study and exhibit his abilities. And the community should supply the families educating invalid children with moral support.